SHOCK! Three Simulated Case Series for Medical Students - Paul Ko; Matthew Sarsfield; Jennifer Campoli; Rodney Freeman; Kara Welch (Association of American Medical Colleges, 2014)
Abstract This resource contains a set of three high-fidelity simulation cases designed to be given in a 3-hour block to third- and fourth-year medical clerkship students during their rotation in the emergency department. The cases are independent but build on each other to give the learner a comprehensive understanding of shock and the management of shock in an emergency department setting. Ideally, the three cases are to be given back-to-back in a set block of time for maximal effect and learning. This simulated case has been used with more than 360 students during the emergency medicine clerkship. We believe these three cases highlight key and important types of shock that students will typically see and need to know how to manage. This simulation series has been extremely well-received by students and the cases have been refined to its current form through 3 years of implementation.